Cheating identifiable (k, n) threshold quantum secret sharing scheme - Yan, Chenhong; Li, Zhihui; Liu, Lu; Lu, Dianjun (Quantum information processing, 2022)
Threshold quantum secret sharing (TQSS) is a quantum cryptography technique that is used to split and reconstruct secret information. It is an important tool for ensuring information security and data confidentiality in the quantum communication environment. TQSS is mainly used to solve the problems of absence and dishonesty among participants. However, most existing TQSS can only detect the fact that one or more of the participants are cheating, and they cannot identify who is the cheater. In this paper, we propose a cheating identifiable ( k , n ) TQSS scheme on a single d -level quantum system. The dealer, Alice, performs a unitary transformation on two identical initial quantum states and signs one of the states. Then, she sends them to the first participant. After the quantum message is validated, the first participant performs his particular unitary transformation on two quantum states. Our scheme employs the voting mechanism, which not only has the ability to identify cheaters but also resists several typical attacks as well as denial and forgery attacks.